KAJIAN FEMINISME TOKOH UTAMA DALAM NOVEL KHUTBAH DI BAWAH LEMBAH KARYA S. JAI - Yunita Yunita; Martono Martono; Christanto Syam (Universitas Tanjungpura, 2019)
AbstractThe study of feminism of the main character in the novel Khutbah di Lembah Bawah by S. Jai and the plan for implementing learning in this school was raised because it discussed literary works with an awareness of gender differences related to culture, literature, and real adventures. This research used descriptive method, in a form fquallitative. The approach of that was used in this research is Kritik Sastra Feminism. The data of this research was novel Khutbah di Bawah Lembah by S.Jai and the data that were collected is the data of the feminism of the main character. The result of the position and role of the main character in the family and society are: 1) the position of the main character in the family (a) as a wife, (b) as a mother. 2) the position of the main character in the society (a) as a cigarette labourer in factory. The role of the main character in the family is as a house wife whereas the role of her in the society is as a cigarette labourer in factory in which she was spent her time in the factory. The result of the unjustified gender in main character (1) Gender and Marginalisation, (2) Gender and stereotype, (3) Gender and work load, (4) gender and violance. The result of main character' sstruggle (1) Provides understanding, (2)Expressing an opinion. Based on the data analysis, this research resulted a conclusion which are (1) the position and role of the main character in the family and society, (2) the form of gender in justification of the main character, (3) the struggle of the main character. Keywords: Main Character’s Feminism